2010
DOI: 10.1111/j.1600-079x.2010.00759.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin, cardiolipin and mitochondrial bioenergetics in health and disease

Abstract: :  Melatonin is a natural occurring compound with well‐known antioxidant properties. Melatonin is ubiquitously distributed and because of its small size and amphiphilic nature, it is able to reach easily all cellular and subcellular compartments. The highest intracellular melatonin concentrations are found in mitochondria, raising the possibility of functional significance for this targeting with involvement in situ in mitochondrial activities. Mitochondria, the powerhouse of the cell, are considered to be the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
309
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(314 citation statements)
references
References 156 publications
(215 reference statements)
4
309
0
1
Order By: Relevance
“…Melatonin has pleiotropic bioactivities including as a highly effective antioxidant and free radical scavenger (Beyer et al 1998, Gitto et al 2009, Chahbouni et al 2010, Paradies et al 2010. Melatonin has protective effect against heart and brain ischemia/reperfusion injuries depending on its antioxidant and free radical scavenging properties (Paradies et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melatonin has pleiotropic bioactivities including as a highly effective antioxidant and free radical scavenger (Beyer et al 1998, Gitto et al 2009, Chahbouni et al 2010, Paradies et al 2010. Melatonin has protective effect against heart and brain ischemia/reperfusion injuries depending on its antioxidant and free radical scavenging properties (Paradies et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin has protective effect against heart and brain ischemia/reperfusion injuries depending on its antioxidant and free radical scavenging properties (Paradies et al 2010). Melatonin has a regulatory role in MMP-mediated physiological processes and major human diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown that melatonin improves mitochondrial function, reduces mitochondrial oxidative status, and increases the activity of the respiratory chain [146,148]. Melatonin, but not other antioxidants (e.g., vitamins C and E, N-acetylcysteine) is highly efficient in maintaining mitochondrial glutathione homeostasis in extremely oxidative conditions, closing the mitochondrial permeability transition pore [149] and promoting mitochondrial survival [150,151].…”
Section: Function As a Free Radical Scavengermentioning
confidence: 99%
“…Acuña-Castroviejo et al documented that melatonin counteracted mitochondrial oxidative damage induced by t-butyl hydroperoxide, recovering glutathione levels and ATP production [45,46] . These data, along with other findings, suggest that melatonin regulates mitochondrial homeostasis [47] .…”
Section: Discussionmentioning
confidence: 60%